Analysis of Marketing Mix Strategy Mix on Sales in Batik Quu Ciwaringin - Widya Widya; Haliza Amera; Dini Selasi (Publikasi Indonesia, 2024)
The phenomenon of digitalisation has affected many aspects of daily life, including family and business life. Increased flexibility and adaptability are necessary for businesses to deal with constant change. The concept of the marketing mix (4Ps: Product, Price, Promotion, Distribution) has evolved into 7Ps with the addition of People, Process, and Physical Evidence. The batik industry, including QUU Ciwaringin Batik in Cirebon, West Java, has great potential to utilise digital marketing strategies to increase sales and consumer loyalty. This study aims to identify the most significant marketing factors in increasing batik sales. With a descriptive qualitative approach, data is collected through interviews, observation, and documentation. Results show that product quality and promotional strategies are the main factors affecting sales. Batik QUU Ciwaringin offers high-quality products with various types of fabrics, such as silk and cotton, as well as custom design services. Effective promotion through exhibitions, cooperation with hotels, and online marketing, despite the constraints in digital content management. Promotion through exhibitions and word-of-mouth is proven to increase visibility and sales. Thus, the implementation of the right 7P marketing mix strategy can support the growth and competitiveness of QUU Ciwaringin Batik in the Indonesian batik market, helping them face challenges and take advantage of opportunities in the digital era.